2000
DOI: 10.1007/s004320000120
|View full text |Cite
|
Sign up to set email alerts
|

Tumor invasion is inhibited by phosphorylated ascorbate via enrichment of intracellular vitamin C and decreasing of oxidative stress

Abstract: Tumor metastasis and invasion were shown to be inhibited by the 2-O-phosphorylated form (Asc2P) of L-ascorbic acid (Asc); intact Asc did not inhibit tumor invasion when added once, but appreciably inhibited it upon repeated addition. The anti-metastatic effect is attributable to a marked enrichment of intracellular Asc by Asc2P, subsequently dephosphorylated. Asc2P scavenged most of the intracellular reactive oxygen species (ROSin), and notably inhibited production of matrix metalloproteases and cell motility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
1
29
2
Order By: Relevance
“…This is in accordance with previous research which showed that a derivative of AA, phospho-ascorbyl palmitate, had an antimetastatic effect on fibrosarcoma and melanoma cell lines by inhibiting the production and enzymatic activity of matrix metalloproteinases (MMP-2 and MMP-9) (34). It was also shown by Nagao et al that it takes repeated supplementation of L-ascorbic acid to inhibit tumor invasion by inhibiting the production of MMPs and cell motility (35), which would explain the high dose of AA required to induce an effect in our tested cell lines. While the mechanism behind MMP-2 expression is mostly unknown (36), the functional activity of MMPs is known to be detained by tissue inhibitors of metalloproteinases (TIMPs) and to be impacted by reactive oxygen species (roS), where excess production of roS, in association with the myeloperoxidase enzyme, would eventually inactivate MMPs (37).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This is in accordance with previous research which showed that a derivative of AA, phospho-ascorbyl palmitate, had an antimetastatic effect on fibrosarcoma and melanoma cell lines by inhibiting the production and enzymatic activity of matrix metalloproteinases (MMP-2 and MMP-9) (34). It was also shown by Nagao et al that it takes repeated supplementation of L-ascorbic acid to inhibit tumor invasion by inhibiting the production of MMPs and cell motility (35), which would explain the high dose of AA required to induce an effect in our tested cell lines. While the mechanism behind MMP-2 expression is mostly unknown (36), the functional activity of MMPs is known to be detained by tissue inhibitors of metalloproteinases (TIMPs) and to be impacted by reactive oxygen species (roS), where excess production of roS, in association with the myeloperoxidase enzyme, would eventually inactivate MMPs (37).…”
Section: Discussionsupporting
confidence: 56%
“…In addition to its effects on HIV replication (29)(30)(31)(32)(33), and its anticancer effects (17), AA has shown inhibitory effects on matrix metalloproteinases (34,35). In our study, ascorbic acid was only effective against the MMP-2 gelatinolytic activity at the highest dose applied in each of the four malignant cell lines and this effect was independent of transcription and, at least in the case of the HTLV-1-negative cell lines, might be related to the AA inhibitory effect on translation.…”
Section: Discussionmentioning
confidence: 99%
“…The latter peroxide may be a cause for spontaneous invasion of AH109A cells, because tumor cells are known to produce a large amount of ROS compared with normal cells (Szatrowski and Nathan 1991). Phosphorylated ascorbate is also reported to inhibit tumor invasion by decreasing oxidative stress (Nagao et al 2000). .…”
Section: Discussionmentioning
confidence: 99%
“…60 In contrast, ROS are key participants in the progression cancer. Scavenging of ROS leads to diminished peritoneal tumor recurrence, 61 inhibits production of matrix metalloproteinase and cell motility 62 and inhibits degradation of the basement membrane. 63 Through these mechanisms, antioxidants might prevent tumor invasion or metastasis in prostate cancer cells.…”
Section: Effect Of Genistein On Antioxidant Enzymes Activities In Lncmentioning
confidence: 99%